Après la certification B2i, vers des compétences sous-jacentes et socio-numériques ? - Thierry Gobert (Université de Provence, 2012)
Digital competency based training is an alternative to the teaching of data processing and e-supported office work. Boyardis distinguishes competencies from abilities and skills often mentioned as e-skills in European referentials. This approach is interesting for consideration of the training practices in the present context where a lack of interest for the principle of operation of tools goes together with huge interest for their utilization. That is why the study is based on a participative observation of two homogeneous groups of subjects having completed or not a B2i training (based on digital competencies) during the year preceding their entering the IUT (University Institute of Technology). The article first exposes the theoretical references and the methodology used for the study. It then describes the observations in reference to the competencies proposed in the method called Competency based training and in the B2i referential for high school level. The results are related to underlying competencies, social behaviour within the working group and also the completion of tasks themselves.